Ledtidsreducering på LKAB Wassara : Möjligheten att utföra lego-processer i egen regi - Bäcklund, Stefan; Olofsson, Janna (2013)
This paper is a thesis paper for the master program in industrial design engineering at Luleå University of Technology. The focus of the project was to reduce the lead times in LKAB Wassara’s production system through focusing on the processes that are currently made by contract manufacturers. The purpose was to evaluate if some of the processes could be beneficially made by Wassara themselves. The types of processes that were analyzed were heat-treatments, such as nitro carburizing and hardening, and machining such as grinding and honing. LKAB Wassara produces water driven DTH (down the hole) hammers for drilling in mining and construction industries. The longest total process time for a component in Wassara’s production was ten weeks, of which 30 workdays went to lead times at contract manufacturers and 14 workdays for transportation. If Wassara could perform some of the processes in their own facilities it could reduce lead times just by removing the need for transportation. The utilization was calculated for the processes and the ones with low utilization were considered unnecessary. Calculations of the cost for producing in-house were compared to the cost of using contract manufacturers. Capital budgeting calculations were made for the two economically beneficial processes, which were grinding and deep hole drilling. These were then evaluated using the requirements specification where the grinding operation was the process to finally be recommended to the company as the most beneficial solution. Validerat; 20130605 (global_studentproject_submitter)